Feto-Maternal Outcome in Antepartum Hemorrhage : A Study in A Tertiary Care Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Antepartum Hemorrhage (APH) is a terrible obstetric emergency associated with maternal and fetal morbidity and mortality worldwide. Objective of this study was to asses the maternal and fetal outcomes as well as to formulate the preventive measures for reducing maternal and fetal complications in patients with APH. Materials and methods: This prospective observational study was conducted at Chattagram Maa-O-Shishu Hospital Medical College, from January to December 2021, on all admitted pregnant women with APH more than 28 weeks gestation. Detailed history, clinical examination, associated conditions, mode of delivery, fetal conditions and investigations were analyzed. Results : A total of 113 APH Cases were reported amongst 5724 pregnant women with its incidence about 2%. The most common cause of APH was placenta previa 80(70.8%) followed by abruptio placenta 28 (24.8%), unexplained 3 (2.7%) and local 2(1.7%) causes. APH was found commonly in patients 72(64%) with age group between 26-30 years, multigravida 95(84%), pregnancy induced hypertension 36 (PIH 32%) previous history of caesarean section 34(30%) and curettage 22(19.2%). Most of the cases 83 (73.5%) were terminated at 34-36 weeks of gestation. There was 1( 0.9%) maternal mortality. However, pregnancy complications were remarkably higher, most common maternal complications were postpartum hemorrhage 45(40%) and maternal shock 6 (5.1%). The commonest mode of delivery was caesarean section 83(73.5%) and in 1(0.9%) case peripartum hysterectomy was needed. Perinatal complications were prematurity 94 (83.1%), perinatal asphyxia 51(45%), stillbirth 26( 23%) and most common causes of early neonatal death were prematurity and neonatal sepsis. Conclusions: APH is associated with significant maternal and fetal morbidity as well as mortality which could be reduced by regular antenatal care, early detection and early referral to higher centers. Better facilities for caesarean section, availability of blood bank and multidisciplinary approach with a good NICU can improve maternal and fetal outcome of APH patients. The incidence of fetal mortality due to abruptio placenta still remains high.Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 57-62